Complex genetic background in a large family with Brugada syndrome. Issue 1 (27th January 2015) - Saber, Siamak; Amarouch, Mohamed‐Yassine; Fazelifar, Amir‐Farjam; Haghjoo, Majid; Emkanjoo, Zahra; Alizadeh, Abolfath; Houshmand, Massoud; Gavrilenko, Alexander V.; Abriel, Hugues; Zaklyazminskaya, Elena V.
Abstract: The Brugada syndrome (BrS) is an inherited arrhythmia characterized by ST‐segment elevation in V1 –V3 leads and negative T wave on standard ECG. BrS patients are at risk of sudden cardiac death (SCD) due to ventricular tachyarrhythmia. At least 17 genes have been proposed to be linked to BrS, although recent findings suggested a polygenic background. Mutations in SCN5A, the gene coding for the cardiac sodium channel Nav 1.5, have been found in 15–30% of index cases. Here, we present the results of clinical, genetic, and expression studies of a large Iranian family with BrS carrying a novel genetic variant (p.P1506S) in SCN5A . By performing whole‐cell patch‐clamp experiments using HEK293 cells expressing wild‐type (WT) or p.P1506S Nav 1.5 channels, hyperpolarizing shift of the availability curve, depolarizing shift of the activation curve, and hastening of the fast inactivation process were observed. These mutant‐induced alterations lead to a loss of function of Nav 1.5 and thus suggest that the p.P1506S variant is pathogenic. In addition, cascade familial screening found a family member with BrS who did not carry the p.P1506S mutation. Additional next generation sequencing analyses revealed the p.R25W mutation in KCNH2 gene in SCN5A ‐negative BrS patients. These findings illustrate the complex genetic background of BrS found in this family and the possible pathogenic role of a new SCN5A genetic variant. Abstract : e12256 We present the results of clinical, genetic, and expression studies of a large Iranian family with BrS carrying a novel genetic variant (p.P1506S) in SCN5A . These mutant‐induced alterations found in whole‐cell patch‐clamp experiments lead to a loss of function of Nav1.5 and thus suggest that the p.P1506S variant is pathogenic. Additional next generation sequencing analyses revealed the p.R25W mutation in KCNH2 gene in SCN5A ‐negative BrS family member.